2013
DOI: 10.1016/j.celrep.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Visual Map Shifts based on Whisker-Guided Cues in the Young Mouse Visual Cortex

Abstract: Mice navigate nearby space using their vision and whiskers, and young mice learn to integrate these heterogeneous inputs in perceptual space. We found that cortical responses were depressed in the primary visual cortex of young mice after wearing a monocular prism. This depression was uniformly observed in the primary visual cortex and was eliminated by whisker trimming or lesions in the posterior parietal cortex. Compensatory visual map shifts of responses elicited via the eye that had worn the prism were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 69 publications
0
43
0
Order By: Relevance
“…We found that in mice the PPC integrates visual and whisker information and that the spatial mismatches between this sensory information induce depression of V1 visual responses (Yoshitake et al., ). This plastic change may be based on the same neural circuits identified here, because the inhibitory projection from the PPC to V1 induced short‐term depression of V1 responses.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We found that in mice the PPC integrates visual and whisker information and that the spatial mismatches between this sensory information induce depression of V1 visual responses (Yoshitake et al., ). This plastic change may be based on the same neural circuits identified here, because the inhibitory projection from the PPC to V1 induced short‐term depression of V1 responses.…”
Section: Discussionmentioning
confidence: 97%
“…As a visual stimulus, we used a red LED or grating pattern that was visualized using a liquid crystal display as previously described (Hishida et al., ; Yoshitake et al., ). As a visual stimulus, we used a red LED ( λ , 613 nm; diameter, 3 mm; TLSH160 (F), Toshiba), which was placed 15 cm away from the mouse's right eye at 45° in the horizontal plane and was turned on for 0.2 or 5.0 s (Figure 3d,e) in each trial.…”
Section: Methodsmentioning
confidence: 99%
“…In mice with disrupted Pcdha or Pcdhg genes, axons of olfactory neurons, retinal ganglion cells, or Ia proprioceptive neurons project properly to their final targets, but once there, fail to form properly distributed terminal arbors [47, 48, 57, 58, 79-81; Table 1]. In contrast, disruption of Pcdh7, Pcdh17, or Pcdh18b results in non-existent or shorter axons in cortical neurons, retinal ganglion cells, motor neurons, or amygdala neurons [77, 85-88, 92; Table 1].…”
Section: Discussionmentioning
confidence: 99%
“…These retinogeniculate terminals seemed to project appropriately early on in development, only forming aberrant aggregates between postnatal day (P)10 and P14, just before eye opening and refinement of retinogeniculate projections. Pcdha mutant mice exhibited reduced visual acuity, but the orientation and direction selectivity of neurons in the primary visual cortex were apparently normal [57,81]. Together, these studies from the Yagi group strongly support a crucial role for α-Pcdhs in the proper targeting and refinement of long axonal projections in the CNS.…”
Section: Roles In Axon Outgrowth and Targetingmentioning
confidence: 98%
“…Loss of the Pcdh α gene cluster's functions in mice induces defects in olfactory sensory-axon coalescence, serotonergic axon arborization, retinogeniculate axon targeting, and in the cortico-cortical pathway between the primary somatosensory cortices in both hemispheres, as well as impaired fear learning and sensory integrations of perceptual space, which occur in the cortex (Fukuda et al, 2008; Hasegawa et al, 2008, 2012; Katori et al, 2009; Yoshitake et al, 2013; Yamashita et al, 2012; Meguro et al, 2005). On the other hand, Pcdh γ mutants die after birth with repetitive tremors associated with massive interneuron apoptosis and synapse loss in the spinal cord (Wang et al, 2002; Weiner et al, 2005; Prasad et al, 2008).…”
Section: Introductionmentioning
confidence: 99%